2000
DOI: 10.1055/s-2000-8539
|View full text |Cite
|
Sign up to set email alerts
|

Essential Moiety for Antimutagenic and Cytotoxic Activity of Hederagenin Monodesmosides and Bisdesmosides Isolated from the Stem Bark of Kalopanax pictus

Abstract: For the elucidation of the antimutagenic and cytotoxic principles from the stem bark of Kalopanax pictus, seven isolated components of this crude drug were tested in the Ames test and the MTT test. Hederagenin and its monodesmosides, kalopanaxsaponin A and I in addition to its bisdesmosides, kalopanaxsaponin B and H, showed potent antimutagenic activities against aflatoxin B 1 (AFB 1 ). However, they had no inhibitory effects on mutagenicity induced by the direct mutagen, N-methyl-N¢ ¢-nitro-N-nitrosoguanidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 13 publications
3
50
0
Order By: Relevance
“…These compounds diminished aflatoxin B 1 (AFB 1 )-induced mutagenesis but had no effect on mutagenesis caused by N-methyl-N'-nitro N-nitrosoguanidine (MNNG). This suggested that hederagenin and its 3-0-glycosides might efficiently prevent the metabolic activation of AFB 1 or scavenge the electrophilic intermediate capable of inducing mutation [75]. It was also shown that the mutagenic potential of aflatoxin B 1 could be inhibited by kaikasaponin III and tectorigenin from Pueraria thumbergiana (Leguminosae).…”
Section: Antimutagenic Activity Of Oa and Ua And Their Derivativesmentioning
confidence: 76%
“…These compounds diminished aflatoxin B 1 (AFB 1 )-induced mutagenesis but had no effect on mutagenesis caused by N-methyl-N'-nitro N-nitrosoguanidine (MNNG). This suggested that hederagenin and its 3-0-glycosides might efficiently prevent the metabolic activation of AFB 1 or scavenge the electrophilic intermediate capable of inducing mutation [75]. It was also shown that the mutagenic potential of aflatoxin B 1 could be inhibited by kaikasaponin III and tectorigenin from Pueraria thumbergiana (Leguminosae).…”
Section: Antimutagenic Activity Of Oa and Ua And Their Derivativesmentioning
confidence: 76%
“…Logarithmic phase human liver cells of L02 were treated essentially according to the method described previously (19). Cells were seeded into 96 well plates and incubated overnight.…”
Section: Technologymentioning
confidence: 99%
“…KPA and KPI reduced the vascular permeability, and KPA was more effective than KPI. When the biological activities of kalopanaxsaponins were investigated in hyperglycemia, 4,7) cytotoxicity, 5) mutagenicity, 13) and hepatotoxicity model, 14) KPA was found to be the most active compound. In this FCA-induced rat rheumatoid arthritis model, KPA was also effective.…”
Section: Time Course Of Metabolism Of Kpk and Kpj By Human Intestinalmentioning
confidence: 99%